The Effect of Questioning Strategy and Students' Motivation Toward Reading Comprehension of Narrative Text at The Eleventh Grade Social Science of SMA Negeri 1 Talamau Pasaman Barat - Yessy Marzona; Widya Juli Astria (Jurnal Ilmiah Pendidikan Scholastic, 2019)
In teaching reading comprehension, teaching strategy and motivation influence students’ reading comprehension. Strategy which was used in this experimental research was Questioning strategy. Questioning strategy can be used as a variation of teaching strategy in teaching reading comprehension. The purpose of this research was to find out the effect of questioning strategy and students’ motivation toward reading comprehension of narrative text. This research was an experimental research with factorial design 2x2. It was conducted at SMA Negeri 1 Talamau Pasaman Barat. The population of this research was eleventh grade social science students with total population of 40 students. The sample was taken by using total sampling; so all of population was taken as sample. XI IPS 2 was experimental class and XI IPS 1 as control class. The instruments of this research were reading comprehension test and questionnaire. The data was analyzed by two ways ANOVA (ANOVA 2x2). The results of this research are (1) Reading comprehension of students who are taught by questioning strategy is better than reading comprehension of students who are taught by conventional strategy. Fo = 196.582 > Ft = 2.69, it means that Ha is accepted. (2) There is no interaction between strategy and students’ motivation toward reading comprehension. Fo = 0.012 < Ft = 2.69, it means that Ha is rejected. When no interaction is present it means that these two strategies did not influence each other so we do not need to continue for hypothesis 3 and hypothesis 4. In short; questioning strategy can be used as a teaching strategy in teaching reading comprehension at SMA Negeri 1 Talamau Pasaman Barat. Other researchers are suggested to do futher research about questioning strategy dealing with of the skills.